The collected biblical writings of T.C. Skeat - Skeat, T. C. (Novum Testamentum, Supplements, 2004)
A high proportion of the many articles published by the papyrologist T.C. Skeat (1907-2003), a former Keeper of Manuscripts at the British Museum, concerns the New Testament. This present collection gathers together papers on Biblical and related matters contributed by Skeat for over sixty years to various publications. The book divides these into three sections: ancient book production, studies on particular Biblical manuscripts and textual criticism. In his Introduction J.K. Elliott assesses the importance of Skeat's work and he incorporates from personal correspondence some of Skeat's later thinking on these topics. A full Bibliography of Skeat's writings is included.